PATTERN OF FETAL DEATHS AT A UNIVERSITY HOSPITAL OF SINDH - Khaskheli, Meharunnissa; Baloch, Shahla; Khushk, Imdad A.; Shah, Shaheen Sharf (Journal of Ayub Medical College Abbottabad, 2007)
Background: Perinatal mortality is a significant public health problem throughout the world. Its prevalence is quite high in the developing countries on account of number of factors. Most of the causes are treatable and fetal outcome can be improved by provision of good health care facilities during antepartum and intrapartum periods and through public education regarding reproductive health and better utilization of health services.Objective: To determine the pattern of intrauterine fetal deaths before or in the process of labor in our tertiary care set up. Methods: This descriptive case series was conducted at Department of Obstetrics and Gynaecology (unit-IV) at Liaquat University Hospital, Jamshoro, Sindh,from April 2002 to October 2003. In total, 50 intrauterine fetal deaths from 24 weeks of gestation to full term pregnancy were analyzed. The case records of all the women were evaluated and data collected regarding their age, period of gestation, clinical features, antenatal records, previous obstetrical history, labor, mode of delivery as well as complications during or after the labor. Results: Out of 697 deliveries, 50 (7.17%) babies were still born. Of these 84% were fresh still born. The commonest factors were antepartum hemorrhage (30%), mismanaged labor (26%), premature rupture of membranes (26%) and congenital anomalies (16%). Conclusion: Majority of fetal deaths in our set up are due to avoidable factors. Hence, there is strong need to improve the quality of care by proper antenatal care, identification of high risk cases and referral to tertiary care hospitals for proper management to prevent morbidity and mortality in this regard. Keywords: Intrauterine; Fetal death; Causes; Prevention; Mortality